2017
DOI: 10.6002/ect.2016.0068
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Infections are highly prevalent during the first year after transplant. Prevention and effective antibiotic therapy can reduce the related adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Our readmission rate is much higher than the infection-related readmissions found in the United States Renal Data System (12%) [ 8 ] and Canada (21% within 30 days and 28.1% within 90 days) [ 15 ]. However, it is similar to the findings of studies from Iran (51% and 49.6%) [ 5 , 16 ]. The tendency of increased infectious events after transplant has been attributed to the use of immunosuppressive drugs, exposure to nosocomial pathogens, and the need for invasive intravascular and urinary devices.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our readmission rate is much higher than the infection-related readmissions found in the United States Renal Data System (12%) [ 8 ] and Canada (21% within 30 days and 28.1% within 90 days) [ 15 ]. However, it is similar to the findings of studies from Iran (51% and 49.6%) [ 5 , 16 ]. The tendency of increased infectious events after transplant has been attributed to the use of immunosuppressive drugs, exposure to nosocomial pathogens, and the need for invasive intravascular and urinary devices.…”
Section: Discussionsupporting
confidence: 91%
“…The most common infection found in our study was UTI, which correlates with studies from Canada [ 15 ], Iran [ 16 ], and Colombia [ 17 ]. In addition, a study from our centre found that 33% of renal transplant recipients had at least one episode of urinary tract infection, and the structural abnormalities, renal stone disease, delay in removing Foley's catheter, and increased post-transplant hospital stay are risk factors leading to UTI in renal transplant recipients [ 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our study investigates the impact of sex and age in a complex patient population at high risk for infections and resulting infectious complications. 36 , 37 , 38 , 39 In the general population, males have a significantly higher COVID‐19‐related mortality than females do. 3 , 5 Estradiol is generally immune enhancing and testosterone immune suppressing 40 thus in the immunocompetent state, females have a more robust anti‐viral immune response than males.…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa was also the most commonly detected pathogen in RI patients. E. coli was reportedly the most commonly isolated pathogen in KTRs in multiple previous studies, [22–24] but the etiology of RI was not evaluated in these studies. In a study investigating potential therapeutic targets, P. aeruginosa was the sixth most common repeat-occurrence pathogen.…”
Section: Discussionmentioning
confidence: 99%